BOAS PRÁTICAS REGULATÓRIAS E RESPONSABILIDADE SOCIAL: ANÁLISE DA PARTICIPAÇÃO DO SETOR PRIVADO NO ÂMBITO DO SUBGRUPO DE TRABALHO Nº3 DO MERCOSUL - Goulart, Fernando Antônio Leite (2006)
Taking into account the concepts of social responsibility, this study aims to analyse critically the participation of private sector in the harmonisation process of technical regulations and conformity assessment procedures in Working Subgroup 3 of Mercosur. The harmonisation of technical regulations and conformity assessment procedures is one of the outstanding challenges to the creation of an actually integrated economic bloc. To Mercosur, the benefits to govern and private sector shall be regarded in the negotiations carried out by Working Subgroup 3 (Technical Regulations and Conformity Assessment), i.e., gathering companies economic interests and govern concerning on citizens safety and sustainable development. By means of a case study about the establishment of the Mercosur Technical Regulation on Safety for Toys, this study aims to ally social responsibility concepts to the legal framework of Mercosur and World Trade Organisation, recommending the adoption, by private sector, of Conduct Codes aligned to the premises of social responsibility, aiming at a better participation on the harmonisation process carried out by Working Subgroup 3.